ISLAMIC EDUCATION IN RESPONSE TO THE CHALLENGES OF EDUCATION IN INDONESIA - Achmad Asrori; Sunarto Sunarto (Ri'ayah: Jurnal Sosial dan Keagamaan, 2021)
In addition to playing a role in preparing humans to enter the future, education also has a relationship with social transformation, and vice versa, various patterns of the education system describe the patterns, traditions, social culture of the existing society. So what is important to note is that an education system is built to carry out the "community mandate", namely to channel its members to certain positions. From the background of the above problems, it can be formulated as follows: What is the substance of Islamic education in the context of responding to the challenges of the world of education in Indonesia ?; How is the development of Islamic Education in the context of responding to the challenges of the world of education in Indonesia ?; How are the solutions for Islamic education in the context of responding to the challenges of the world of education in Indonesia? The research objectives are; describe the substance of Islamic education in the context of responding to challenges in the world of education in Indonesia; identify developments in Islamic education in the context of responding to challenges in the world of education in Indonesia; exploring alternative Islamic Education Solutions in the context of responding to challenges in the world of education in Indonesia. This research includes library research (library research ), which is research that collects data and information with the help of various materials contained in the literature (books). The data collection method used in this research is the documentation method, namely by searching for and collecting data and books which are the primary and secondary data sources, while the data collected can be in the form of notes, transcripts, books, newspapers, magazines, inscriptions, note-taking. meeting. The data analysis method used in this study is qualitative analysis. The results of the study show that up to now 91.4% of the total madrasah (MI, MTs and MA) in Indonesia are privately owned, while the rest are state-owned. This data implies the high spirit of independence of the Islamic community in implementing madrasa education, which is more driven by religious and preaching spirit, so that it can accommodate a large number of students and simultaneously contribute to the success of the 9 (nine) years compulsory education. However, this religious and preaching spirit has generally not been accompanied by professionalism in madrasa management.